2020
DOI: 10.1101/2020.04.09.20058651
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Scaling diagnostics in times of COVID-19: Colorimetric Loop-mediated Isothermal Amplification (LAMP) assisted by a 3D-printed incubator for cost-effective and scalable detection of SARS-CoV-2

Abstract: 2 3 be limited. Moreover, the portability, ease of use, and reproducibility of this strategy make 4 1 it a reliable alternative for deployment of point-of-care SARS-CoV-2 detection efforts 4 2during the pandemics. 4 3 4 4

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 50 publications
0
19
0
Order By: Relevance
“…Most isothermal amplification steps require incubation at elevated temperatures around 60°C. To facilitate isothermal amplification at remote testing facilities, González-González et al developed a 3D-printed water circulator that can act as a heat block for LAMP amplification and have demonstrated the ability to detect as few as 62 viral RNA molecules after 1 hour of incubation (González-González et al 2020). To make RT-PCR more accessible for remote testing, Wee et al have demonstrated a rapid, extraction-free PCR protocol that can detect 6 SARS-CoV-2 RNA copies using a portable thermocycler (Wee et al).…”
Section: Other Nats ("Thinking Outside the Box")mentioning
confidence: 99%
“…Most isothermal amplification steps require incubation at elevated temperatures around 60°C. To facilitate isothermal amplification at remote testing facilities, González-González et al developed a 3D-printed water circulator that can act as a heat block for LAMP amplification and have demonstrated the ability to detect as few as 62 viral RNA molecules after 1 hour of incubation (González-González et al 2020). To make RT-PCR more accessible for remote testing, Wee et al have demonstrated a rapid, extraction-free PCR protocol that can detect 6 SARS-CoV-2 RNA copies using a portable thermocycler (Wee et al).…”
Section: Other Nats ("Thinking Outside the Box")mentioning
confidence: 99%
“…Proteinase K treatment both protects free RNA by inactivating nucleases, and releases particle-bound RNA. Incorporating quantitative colorimetric decomposition and analysis will enhance sensitivity and interpretability of borderline samples in future experiments 22 .…”
Section: Validation On Clinical Samplesmentioning
confidence: 99%
“…These results contrast sharply with previous studies showing that incubation times of forty to fifty minutes are required for reliable color development and end-point detection of SARS-CoV-2 colorimetric LAMP assays. 12,29,32 This indicates that our simple instrument is able to detect subtle changes in the optical characteristics of the reaction that occur before easily observable color changes. The second luminance derivative peaks (L’ MAX2 ) in our instrument are much larger than L’ MAX1 and are typically observed between 25-35 minutes into the reaction which is more consistent with times required for endpoint assays, suggesting that this shift is primarily due to the spectral shift in the pH indicator.…”
Section: Resultsmentioning
confidence: 92%
“…Colorimetric assays were run ten minutes longer than fluorescent assays for a total time of 40 minutes to compensate for the relatively slow color change of the phenol red indicator that has been demonstrated to take forty to fifty minutes to detect single copy numbers of SARS-CoV-2 genomes in previous studies. 29,30 All subsequent colorimetric assays were performed under optimal conditions: 40 mM GuHCl and incubated at 65°C for 40 minutes.…”
Section: Resultsmentioning
confidence: 99%